A Fully-Printed Wearable Bandage-Based Electrochemical Sensor with pH Correction for Wound Infection Monitoring - Kaewpradub, Kanyawee; Veenuttranon, Kornautchaya; Jantapaso, Husanai; Mittraparp‑arthorn, Pimonsri; Jeerapan, Itthipon (Nano-Micro Letters, 2024)
Wearable sensing systems have been designed to monitor health conditions in real-time by detecting analytes in human biofluids. Wound diagnosis remains challenging, necessitating suitable materials for high-performance wearable sensors to offer prompt feedback. Existing devices have limitations in measuring pH and the concentration of pH-dependent electroactive species simultaneously, which is crucial for obtaining a comprehensive understanding of wound status and optimizing biosensors. Therefore, improving materials and analysis system accuracy is essential. This article introduces the first example of a flexible array capable of detecting pyocyanin, a bacterial virulence factor, while correcting dynamic pH fluctuations. We demonstrate that this combined sensor enhances accuracy by mitigating the impact of pH variability on pyocyanin sensor response. Customized screen-printable inks were developed to enhance analytical performance. The analytical performances of two sensitive sensor systems (i.e., fully-printed porous graphene/multiwalled carbon nanotube (CNT) and polyaniline/CNT composites for pyocyanin and pH sensors) are evaluated. Partial least square regression is employed to analyze nonzero-order data arrays from square wave voltammetric and potentiometric measurements of pyocyanin and pH sensors to establish a predictive model for pyocyanin concentration in complex fluids. This sensitive and effective strategy shows potential for personalized applications due to its affordability, ease of use, and ability to adjust for dynamic pH changes. Highlights: 1 The first example of a flexible array capable of detecting pyocyanin, a bacterial virulence factor, while correcting dynamic pH fluctuations. 2 Developed a screen-printable conductive nanocomposite ink for fabricating the pyocyanin sensor and utilized a polyaniline/carbon nanocomposite as a pH-sensitive film for the pH sensor. 3 Customized inks are advantageous in terms of flexible printed sensing array integrated onto a bandage surface, capable of monitoring both pyocyanin and pH levels in wound exudate.